Patología del muñón gástrico - Soto Cordano, José; Bergalli, Luis; Campos, Néstor; Castiglioni, Juan C; Iraola, María; Sojo, Enrique; Zimmer, Walter; Zubiaurre, Jorge (Cirugía del Uruguay, 1983)
Round Table 33 Congress